Critical Thinking Across the Curriculum: A Vision. - Ennis, Robert H. (Topoi: An International Review of Philosophy, 2018)
This essay offers a comprehensive vision for a higher education program incorporating critical thinking across the curriculum (CTAC) at hypothetical Alpha College, employing a rigorous detailed conception of critical thinking called “The Alpha Conception of Critical Thinking”. The program starts with a 1-year, required, freshman course, two-thirds of which focuses on a set of general critical thinking dispositions and abilities. The final third uses subject-matter issues to reinforce general critical thinking dispositions and abilities, teach samples of subject matter, and introduce subject-specific critical thinking. Subject-matter departmental and other units will make long-range plans for incorporating critical thinking in varying amounts in subject-matter courses, culminating in a written Senior Thesis/Project involving investigating, taking, and defending a position, which reinforce critical thinking abilities and dispositions and increase subject-matter knowledge. Teaching approaches used in the program are involving and based on the principle, “We learn what we use.” Both summative and formative assessment are employed as appropriate. Coordination and support are extensive. Objections and concerns are discussed, and alternatives, including possible transitions, are considered. An extended review of research supports moving toward CTAC.